n = 1 ∑ ∞ 2 n H n F n = ln ( A ) + C B coth − 1 ( E D ) Find D E ( A + B + C ) 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
We know that a Generating Function of the Harmonic Numbers is given by:-
n = 1 ∑ ∞ H n z n = − 1 − x ln ( 1 − x )
Also we know by Binet's Formula that the nth Fibonacci Number is given by F n = 5 φ n − ( 1 − φ ) n
Where φ = 2 1 + 5 is the Golden Ratio .
So we have the following summation:-
5 1 n = 1 ∑ ∞ H n ( ( 2 φ ) n − ( 2 1 − φ ) n )
So using the generating function we have our summation equal to:-
5 1 ( 1 − 2 1 − φ ln ( 1 − 2 1 − φ ) − 1 − 2 φ ln ( 1 − 2 φ ) ) .
Now it is just a matter of Rearrangements. We know coth − 1 ( x ) = 2 1 ln ( 1 − x 1 + x ) .
Using all of these we arrive at the answer:-
ln ( 4 ) + 5 6 coth − 1 ( 5 3 )